Germplasm Collection and Molecular Detection of Endophytic Fungi in Iranian Tall Fescue (Festuca Arundinacea Schreb.) - Nekouei, Mojtaba Khayyam (2001)
Tall fescue is a popular pasture grass grown in many countries. A systematic endophytic fungus, Acremonium coenophialum, lives in a symbiotic association within tall fescue and may impart superior competitiveness to the plant through increased resistance to pests, tolerance to drought and improvements in other agronomic traits. The assessment of the infection status and viability of endophytic fungi would open the possibility of identifying potentially desirable endophyte strains for improving pasture, turf and crop species. Therefore, studies of tall fescue and endophytic fungi in Iran are essential for its improvement and may provide opportunities to produce elite endophyte-infected plant population. Nineteen accessions of tall fescue were collected from various regions of Iran, identified and evaluated for the presence of endophyte based on IPGRl descriptors. The accessions were mainly distributed in the northern and western part of the country with relatively more precipitation. Seven agronomic characteristics under greenhouse and fifteen traits under field conditions were evaluated. Result obtained from cluster analysis grouped the accessions into 3 clusters based on the parameters of the greenhouse and field experiments. Out of the 15 traits, only 10 traits under field conditions showed significant variation among the accessions. The correlation analysis showed that the yield is directly proportional to the number of inflorescence. After greenhouse and field evaluation, the accessions were evaluated for the presence of endophyte. Detection of endophytic fungi in tall fescue seeds showed that 84.2% of the accessions were infected with endophyte at infection rates of 20 to 95%. The results of the endophytic fungi detection in greenhouse-grown and fieldgrown tall fescue seedlings indicated that viable fungal endophyte occurred in 73.3% of total tall fescue accessions evaluated. The in vitro isolation and culture of endophyte confirmed the result obtained from greenhouse and field experiments. The conventional methods for detection of endophyte in tall fescue requires at least 28 days and therefore a rapid and sensitive molecular method was developed to facilitate detection and identification of endophytic fungi in tall fescue. This method could be used for the screening of large number of seed and plant samples. Diagnostic PCR was developed and optimised to evaluate and verify the infection status of collected accessions. The PCR with microsatellite (MS) and internal transcribed spacer (ITS) primers generated DNA fragments of different sizes. The infected accessions yielded amplification products with size ranging from 250 to 400 base pair for MS primers and 550 to 750 base pair for ITS primers. No amplification product was detected on the uninfected seedlings. The results indicated that ITS primers (ITS1 and ITS4) and also MS primers (MSF and MSR) appeared to be useful for the detection of endophytic infection of tall fescue accessions.